Thrilling Encounters in Social Settings: A Retelling of The Eyes of Darkness by Dean Koontz - Ali, Muhammad Ilham; Jannah, Sabrina Wardhatul; Pabur, Herminus Efrando; Katili, Yayu Anggraini H (Tamaddun Life, 2024)
This study analyzes the social situations depicted in the novel "The Eyes of Darkness" by Dean Koontz, focusing on themes such as abuse, thriller elements, tragedy, mental health, and the virus. Using a descriptive-qualitative approach, we delve into the novel's narrative to uncover how these themes are portrayed and their implications on the characters and broader societal reflections. The analysis reveals that the novel intricately weaves these social situations to create a compelling story that resonates with real-world issues. Abuse is depicted through the misuse of power and its devastating consequences, while thriller elements introduce suspense and supernatural occurrences that challenge characters' perceptions of reality. Tragedies highlight the unpredictability of life and the resilience needed to overcome adversity. The exploration of mental health, particularly through the character of Tina, emphasizes the impact of grief and trauma and the journey towards healing. Lastly, the portrayal of the virus, notably the Wuhan-400, offers a chillingly prescient reflection of global pandemics, underscoring the ethical considerations in scientific research. This study highlights the novel's relevance in addressing complex human experiences and societal issues, offering valuable insights into the interplay between fiction and reality.